Analisis Kestabilan Lubang Bukaan Tambang Bawah Tanah Berdasarkan Klasifikasi Geomekanika (RMR-System) Site D.25 Lokasi III PT. Dasrat Sarana Arang Sejati, Parambahan, Desa Batu Tanjung, Kecamatan Talawi, Kota Sawahlunto - Ari Ardila; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2021)
From the measurement of several parameters of the RMR method that has been carried out, at Site D.25 Location III for siltstone is in class III (fair rock) with an RMR value of 57 with Stand Up Time is 1200 hours or 50 days with a planned production advance hole width of 3 meters, and coal is in class III (fair rock) with an RMR value of 51 with a Stand Up Time of 600 hours or 25 days with a planned production advance pit width of 3 meters. Based on the RMR weighting data then: if using rock bolt (20 mm diameter fully grouted) with a length of 4 m and a spacing of 1.5-2 m on the walls and roof then add the installation of wire mesh, shotcrete thickness of 50-100 mm on the roof and 30 mm on the wall. If using wood reinforcement, then for the reinforcement of the opening holes, a recommendation for a support system that should be applied to optimize the support to be safe and profitable is obtained, namely with a wood diameter of 20 cm, a distance between supports of 1.5 m and FK 1.5.